Effect of CdS modification on photoelectric properties of TiO2/PbS quantum dots bulk heterojunction. (June 2016) - Shi, Xin; Xu, Jianping; Shi, Shaobo; Zhang, Xiaosong; Li, Shubin; Wang, Chang; Wang, Xueliang; Li, Linlin; Li, Lan
Abstract: TiO2 /PbS(CdS) quantum dots (QDs) bulk heterojunction has been fabricated by successive ionic layer adsorption and reaction method via alternate deposition of PbS and CdS QDs. In comparison with TiO2 /PbS heterojunction, the incident photon to current conversion efficiency was increased almost 50% in the visible region. Meantime, the short-circuit current and open-circuit voltage were enhanced 200% and 35% respectively. The influence mechanism of CdS is related to reduction of trap state density at TiO2 /PbS interface and PbS QDs surface by the discussion of the dark current density–voltage curves, the transient photocurrent response curves and the electrochemical impedance spectra spectroscopy (EIS). Graphical abstract: The figure shows charge transport schematic diagram for TiO2 /PbS(CdS) heterojunction. (The red crosses represent the blocked charge transport process.) Highlights: The TiO2 /PbS(CdS) QDs bulk heterojunction was fabricated by SILAR method. The additional CdS improved the photoelectric conversion properties. The CdS modification can reduce trap states and carriers recombination.